Method for producing positive resist composition and method for forming resist pattern

By filtering a positive resist composition solution through a 20 nm filter to remove foreign matter, the method addresses the issue of contaminant mixing in resist patterns, improving pattern clarity and suitability for semiconductor manufacturing processes.

JP7615662B2Active Publication Date: 2025-01-17ZEON CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020214302
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-23
Publication Date
2025-01-17
Estimated Expiration
2040-12-23

AI Technical Summary

Technical Problem

The challenge in semiconductor manufacturing is the unintentional mixing of foreign substances, particularly metals, into resist patterns formed using positive resists, which is exacerbated by advanced lithography technologies like EUV lithography, necessitating a reduction in foreign matter to achieve fine patterns.

Method used

A method involving the production of a positive resist composition by filtering a solution containing a copolymer through a filter with a particle-excluded diameter of 20 nm or less to remove foreign matter, ensuring the resist pattern has a reduced amount of contaminants.

Benefits of technology

This approach effectively reduces the amount of foreign matter in the resist pattern, enhancing the clarity and quality of the resist pattern formed, suitable for use in etching methods and applications such as printed circuit board manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615662000001
    Figure 0007615662000001
  • Figure 0007615662000002
    Figure 0007615662000002
  • Figure 0007615662000003
    Figure 0007615662000003
Patent Text Reader

Abstract

To provide a new technique whereby: when forming a resist pattern using a positive resist, it is possible to reduce the amount of foreign matter to be mixed in the resist pattern.SOLUTION: A method for producing a positive resist composition includes the step of filtering a solution that contains a copolymer containing a monomer unit (A) represented by formula (I) and a monomer unit (B) represented by formula (II), and a solvent, by causing the solution to pass through a filter having a removable particle size of 20 nm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a positive resist composition and a method for forming a resist pattern. [Background technology]

[0002] Conventionally, in the field of semiconductor manufacturing and the like, copolymers in which the main chain is cleaved and the solubility in a developer is increased by irradiation with ionizing radiation such as electron beams or short-wavelength light such as ultraviolet light (including extreme ultraviolet (EUV)) (hereinafter, ionizing radiation and short-wavelength light may be collectively referred to as "ionizing radiation, etc.") have been used as main-chain scission type positive resists.

[0003] Specifically, for example, Patent Document 1 discloses a positive resist composed of a copolymer containing α-chloroacrylate-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units and α-methylstyrene units as a main chain cleavage type positive resist having excellent heat resistance and sensitivity to ionizing radiation, etc. A resist film is formed from a positive resist composition obtained by dissolving such a copolymer in a solvent, the resist film obtained is exposed, and then the exposed resist film is developed, thereby forming a resist pattern. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2018-154754 A Summary of the Invention [Problem to be solved by the invention]

[0005] Here, there has been a demand for reducing the amount of foreign matter such as metals that unintentionally mix into the obtained resist pattern. In particular, in recent years, EUV lithography technology using EUV has been attracting attention as a technology that has less proximity effect during exposure compared to electron beams and enables fine pattern formation. Under these circumstances, there is an increasing demand for reducing the amount of the above-mentioned foreign matter when forming a resist pattern using a positive resist.

[0006] SUMMARY OF THE PRESENT EMBODIMENTS The present invention has an object to provide a new technique for reducing the amount of foreign matter that gets mixed into a resist pattern when a resist pattern is formed using a positive resist. [Means for solving the problem]

[0007] The present inventors have conducted extensive research to achieve the above object. The present inventors have focused on the manufacturing process of a positive resist composition used to form a resist film. The present inventors have discovered that when preparing a positive resist composition containing a copolymer formed using a specified monomer and a solvent, the inclusion of foreign matter in the resulting resist pattern can be advantageously suppressed by passing a solution containing the copolymer and the solvent through a filter having a particle size exclusion value of a specified value or less to remove foreign matter, and have completed the present invention.

[0008] That is, an object of the present invention is to solve the above-mentioned problems in an advantageous manner, and a method for producing a positive resist composition of the present invention comprises reacting a compound represented by the following formula (I): [ka] [In formula (I), R 1 is a halogen atom, a cyano group, an alkylsulfonyl group, an alkoxy group, a nitro group, an acyl group, an alkyl ester group or a halogenated alkyl group, R 2 is an alkyl group, a halogenated alkyl group, or a structure represented by -L-Ar, where L is a single bond or a divalent linking group, and Ar is an aromatic ring group which may have a substituent; R 3 and R4 are hydrogen atoms, halogen atoms, alkyl groups or halogenated alkyl groups, and may be the same or different. A monomer unit (A) represented by the formula: The following formula (II): [ka] [In formula (II), R 5 , R 6 , R 8 and R 9 are a hydrogen atom, a halogen atom, a carboxyl group, a halogenated carboxyl group, an alkyl group, or a halogenated alkyl group, and may be the same or different from each other, R 7 is a hydrogen atom, an alkyl group, or a halogenated alkyl group, p and q are integers of 0 to 5, and p+q=5; R 6 When multiple are present, they may be the same or different, and R 7 When a plurality of are present, they may be the same or different. The method is characterized in that it includes a step of filtering a solution containing a solvent and a copolymer having a monomer unit (B) represented by the following formula: and passing the solution through a filter having a particle size exclusion diameter of 20 nm or less. In this way, by passing a solution containing the above-mentioned predetermined copolymer and a solvent through a filter having a particle size exclusion diameter of the above-mentioned value or less, it is possible to obtain a positive resist composition in which the amount of foreign matter is sufficiently reduced. In the present invention, the "particle removal size" of a filter means the minimum size of particles that can be removed by the filter. For example, if the particle removal size of a filter is 20 nm, it can remove particles with a diameter (particle size) of 20 nm or more. In the present invention, the phrase "optionally having a substituent" means "unsubstituted or having a substituent".

[0009] Here, in the method for producing a positive resist composition of the present invention, the weight average molecular weight of the copolymer preferably exceeds 30,000. If the weight average molecular weight of the copolymer exceeds 30,000, the clarity of the resist pattern obtained using the positive resist composition can be ensured.

[0010] In the method for producing a positive resist composition of the present invention, it is preferable that the total number of fluorine atoms contained in the monomer unit (A) and the monomer unit (B) is at least 1. When the total number of fluorine atoms in the monomer unit (A) and the monomer unit (B) is at least 1, the filter permeability of a solution containing the copolymer can be improved.

[0011] The present invention also aims to advantageously solve the above-mentioned problems, and provides a method for forming a resist pattern, comprising the steps of forming a resist film using a positive resist composition obtained by any one of the above-mentioned methods for producing a positive resist composition, exposing the resist film to light, and developing the resist film after exposure. By forming a resist pattern using a positive resist composition obtained by any one of the above-mentioned methods for producing a positive resist composition, it is possible to sufficiently reduce the amount of foreign matter that gets mixed into the resulting resist pattern. Effect of the Invention

[0012] According to the method for producing a positive resist composition of the present invention, it is possible to produce a positive resist composition in which the amount of foreign matter is sufficiently reduced. Furthermore, according to the method of forming a resist pattern of the present invention, a resist pattern in which the amount of foreign matter is sufficiently reduced can be formed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described in detail. The method for producing a positive resist composition of the present invention is a method for producing a positive resist composition that contains a main chain scission type positive resist in which the main chain is scissed and the molecular weight is reduced by irradiation with ionizing radiation or the like. The method of forming a resist pattern of the present invention is a method of forming a resist pattern using a positive resist composition obtained by the method of producing a positive resist composition of the present invention. Furthermore, a resist pattern formed by the method for forming a resist pattern of the present invention can be used in an etching method in which a workpiece is etched using the resist pattern as a mask to form a pattern on the workpiece. Such a method for producing a positive resist composition, a method for forming a resist pattern, and a method for etching can be suitably used, for example, when producing printed circuit boards such as build-up boards.

[0014] (Method for Producing Positive Resist Composition) In the method for producing a positive resist composition of the present invention, a solution containing a copolymer as a main chain scission type positive resist and a solvent is filtered through a filter with a particle exclusion diameter of 20 nm or less.

[0015] When the above-mentioned copolymer is irradiated with ionizing radiation or the like (e.g., an electron beam, a KrF laser, an ArF laser, an EUV laser, etc.), the main chain is easily cleaved, resulting in a low molecular weight. In the method for producing a positive resist composition of the present invention, the positive resist composition is produced via the above-mentioned filtration, so it is possible to obtain a positive resist composition in which the amount of foreign matter is sufficiently reduced.

[0016] <Solution> The solution contains a predetermined copolymer as a positive resist, which will be described in detail below, and further contains a solvent. Furthermore, the positive resist composition optionally further contains known additives that can be blended into the resist composition. The solution may contain a polymer other than the copolymer specified as the positive resist, but usually contains only the specified copolymer as the positive resist.

[0017] <<Copolymer>> The copolymer contained in the solution has a given monomer unit (A) and a given monomer unit (B). The copolymer may contain any monomer unit other than the monomer unit (A) and the monomer unit (B). However, the proportion of the monomer unit (A) and the monomer unit (B) in all the monomer units constituting the copolymer is preferably 90 mol % or more in total, and more preferably 100 mol % (i.e., the copolymer contains only the monomer unit (A) and the monomer unit (B)).

[0018] [Monomer unit (A)] The monomer unit (A) has the following formula (I): [ka] [In formula (I), R 1 is a halogen atom, a cyano group, an alkylsulfonyl group, an alkoxy group, a nitro group, an acyl group, an alkyl ester group or a halogenated alkyl group, R 2 is an alkyl group, a halogenated alkyl group, or a structure represented by -L-Ar, where L is a single bond or a divalent linking group, and Ar is an aromatic ring group which may have a substituent; R 3 and R 4 are hydrogen atoms, halogen atoms, alkyl groups or halogenated alkyl groups, and may be the same or different. and represented by the following formula (III): [ka] (In formula (III), R 1 ~R 4 is the same as in formula (I).

[0019] Here, R in formula (I) and formula (III) 1 Examples of halogen atoms that can constitute the above group include a chlorine atom, a fluorine atom, a bromine atom, an iodine atom, and an astatine atom. In addition, R in formula (I) and formula (III) 1 Examples of the alkylsulfonyl group that can constitute the above formula include a methylsulfonyl group and an ethylsulfonyl group. Furthermore, R in formula (I) and formula (III) 1 Examples of alkoxy groups that can constitute the above formula include methoxy, ethoxy, and propoxy groups. In addition, R in formula (I) and formula (III) 1 Examples of acyl groups that can constitute the above formula include a formyl group, an acetyl group, and a propionyl group. Furthermore, R in formula (I) and formula (III) 1 Examples of the alkyl ester group that can constitute the above formula include a methyl ester group and an ethyl ester group. And, R in formula (I) and formula (III) 1 Examples of halogenated alkyl groups that can constitute the above include halogenated methyl groups having 1 to 3 halogen atoms. Among them, from the viewpoint of efficiently obtaining copolymers useful as main chain scission type positive resists, R 1 is preferably a halogen atom, more preferably a chlorine atom.

[0020] Here, R in formula (I) and formula (III) 2 Examples of the alkyl group that can constitute the above group include unsubstituted alkyl groups having 1 to 10 carbon atoms. In addition, R in formula (I) and (III) 2Examples of the halogenated alkyl group that can be constituted include an alkyl group substituted with a fluorine atom. Examples of the alkyl group substituted with a fluorine atom include a 2,2,2-trifluoroethyl group, a 2,2,3,3,3-pentafluoropropyl group, a 2-(perfluorobutyl)ethyl group, a 2-(perfluorohexyl)ethyl group, a 1H,1H,3H-tetrafluoropropyl group, a 1H,1H,5H-octafluoropentyl group, a 1H,1H,7H-dodecafluoroheptyl group, a 1H-1-(trifluoromethyl)trifluoroethyl group, a 1H,1H,3H-hexafluorobutyl group, or a 1,2,2,2-tetrafluoro-1-(trifluoromethyl)ethyl group. Among them, the halogenated alkyl group is preferably a 2,2,2-trifluoroethyl group or a 2,2,3,3,3-pentafluoropropyl group.

[0021] In addition, R in formula (I) and (III) 2 In the case where the structure is represented by -L-Ar, the divalent linking group that can constitute L is not particularly limited, and examples thereof include an alkylene group which may have a substituent, and an alkenylene group which may have a substituent. The alkylene group of the alkylene group which may have a substituent is not particularly limited, and examples thereof include linear alkylene groups such as methylene, ethylene, propylene, n-butylene, and isobutylene, and cyclic alkylene groups such as 1,4-cyclohexylene. Among them, the alkylene group is preferably a linear alkylene group having 1 to 6 carbon atoms such as methylene, ethylene, propylene, n-butylene, and isobutylene, more preferably a linear alkylene group having 1 to 6 carbon atoms such as methylene, ethylene, propylene, and n-butylene, and even more preferably a linear alkylene group having 1 to 3 carbon atoms such as methylene, ethylene, and propylene. The alkenylene group of the alkenylene group which may have a substituent is not particularly limited, and examples thereof include chain alkenylene groups such as ethenylene group, 2-propenylene group, 2-butenylene group, and 3-butenylene group, and cyclic alkenylene groups such as cyclohexenylene group. Among them, the alkenylene group is preferably a straight-chain alkenylene group having 2 to 6 carbon atoms such as ethenylene group, 2-propenylene group, 2-butenylene group, and 3-butenylene group. Among the above, from the viewpoint of sufficiently improving the sensitivity to ionizing radiation and the like, the divalent linking group is preferably an alkylene group which may have a substituent, more preferably a chain alkylene group having 1 to 6 carbon atoms which may have a substituent, still more preferably a linear alkylene group having 1 to 6 carbon atoms which may have a substituent, and particularly preferably a linear alkylene group having 1 to 3 carbon atoms which may have a substituent. From the viewpoint of further improving the sensitivity to ionizing radiation and the like, the divalent linking group capable of constituting L in formula (I) and formula (III) preferably has one or more electron-withdrawing groups. In particular, when the divalent linking group is an alkylene group having an electron-withdrawing group as a substituent or an alkenylene group having an electron-withdrawing group as a substituent, it is preferred that the electron-withdrawing group is bonded to the carbon bonded to O adjacent to the carbonyl carbon in formula (I) and formula (III).

[0022] The electron-withdrawing group capable of sufficiently improving the sensitivity to ionizing radiation or the like is not particularly limited, and may be, for example, at least one selected from the group consisting of a fluorine atom, a fluoroalkyl group, a cyano group, and a nitro group. The fluoroalkyl group is not particularly limited, and may be, for example, a fluoroalkyl group having 1 to 5 carbon atoms. Among them, the fluoroalkyl group is preferably a perfluoroalkyl group having 1 to 5 carbon atoms, and more preferably a trifluoromethyl group. From the viewpoint of sufficiently improving the sensitivity to ionizing radiation and the like, L in formula (I) and formula (III) is preferably a methylene group, a cyanomethylene group, a trifluoromethylmethylene group, or a bis(trifluoromethyl)methylene group, and more preferably a bis(trifluoromethyl)methylene group.

[0023] In addition, R in formula (I) and (III) 2 In the case where the structure is represented by -L-Ar, examples of Ar include an aromatic hydrocarbon ring group which may have a substituent and an aromatic heterocyclic group which may have a substituent.

[0024] The aromatic hydrocarbon ring group is not particularly limited, and examples thereof include a benzene ring group, a biphenyl ring group, a naphthalene ring group, an azulene ring group, an anthracene ring group, a phenanthrene ring group, a pyrene ring group, a chrysene ring group, a naphthacene ring group, a triphenylene ring group, an o-terphenyl ring group, an m-terphenyl ring group, a p-terphenyl ring group, an acenaphthene ring group, a coronene ring group, a fluorene ring group, a fluoranthrene ring group, a pentacene ring group, a perylene ring group, a pentaphene ring group, a picene ring group, and a pyranthrene ring group.

[0025] Furthermore, examples of the aromatic heterocyclic group include, but are not limited to, a furan ring group, a thiophene ring group, a pyridine ring group, a pyridazine ring group, a pyrimidine ring group, a pyrazine ring group, a triazine ring group, an oxadiazole ring group, a triazole ring group, an imidazole ring group, a pyrazole ring group, a thiazole ring group, an indole ring group, a benzimidazole ring group, a benzothiazole ring group, a benzoxazole ring group, a quinoxaline ring group, a quinazoline ring group, a phthalazine ring group, a benzofuran ring group, a dibenzofuran ring group, a benzothiophene ring group, a dibenzothiophene ring group, and a carbazole ring group.

[0026] Furthermore, the substituent that Ar may have is not particularly limited, and examples thereof include an alkyl group, a fluorine atom, and a fluoroalkyl group. Examples of the alkyl group as the substituent that Ar may have include a chain alkyl group having 1 to 6 carbon atoms, such as a methyl group, an ethyl group, a propyl group, an n-butyl group, and an isobutyl group. Examples of the fluoroalkyl group as the substituent that Ar may have include a fluoroalkyl group having 1 to 5 carbon atoms, such as a trifluoromethyl group, a trifluoroethyl group, and a pentafluoropropyl group.

[0027] Among these, from the viewpoint of sufficiently improving the sensitivity to ionizing radiation and the like, Ar in formula (I) and formula (III) is preferably an aromatic hydrocarbon ring group which may have a substituent, more preferably an unsubstituted aromatic hydrocarbon ring group, and even more preferably a benzene ring group (phenyl group).

[0028] Here, R in formula (I) and formula (III) 3 and R 4 Examples of halogen atoms which may constitute the above group include a chlorine atom, a fluorine atom, a bromine atom, an iodine atom and an astatine atom. In addition, R in formula (I) and formula (III) 3 and R 4 Examples of the alkyl group that can constitute the above group include unsubstituted alkyl groups having 1 to 10 carbon atoms. Furthermore, R in formula (I) and (III) 3 and R 4 Examples of the halogenated alkyl group that can constitute the above-mentioned group include an alkyl group substituted with a fluorine atom. Examples of the alkyl group substituted with a fluorine atom include the alkyl group represented by the formula (I) and the formula (III) R 1 Examples of the halogenated alkyl group that can constitute the above group include the same groups as those exemplified above. Among them, from the viewpoint of efficiently obtaining copolymers useful as main chain scission type positive resists, R 3 and R 4 is preferably a hydrogen atom.

[0029] Examples of the monomer (a) represented by the above formula (III) which can form the monomer unit (A) represented by the above formula (I) include methyl α-chloroacrylate, 2,2,2-trifluoroethyl α-chloroacrylate, 2,2,3,3,3-pentafluoropropyl α-chloroacrylate, 2-(perfluorobutyl)ethyl α-chloroacrylate, 2-(perfluorohexyl)ethyl α-chloroacrylate, 1H,1H,3H-tetrafluoropropyl α-chloroacrylate, 1H,1H,5H-tetrafluoropropyl α-chloroacrylate, and 1H,1H,5H-tetrafluoropropyl α-chloroacrylate. -octafluoropentyl, α-chloroacrylic acid 1H,1H,7H-dodecafluoroheptyl, α-chloroacrylic acid 1H-1-(trifluoromethyl)trifluoroethyl, α-chloroacrylic acid 1H,1H,3H-hexafluorobutyl, α-chloroacrylic acid 1,2,2,2-tetrafluoro-1-(trifluoromethyl)ethyl; α-fluoroacrylic acid alkyl esters such as α-fluoroacrylic acid methyl and α-fluoroacrylic acid ethyl; α-trifluoro α-Fluoroalkyl acrylic acid alkyl esters such as methyl methylacrylate and ethyl α-trifluoromethylacrylate; 2,2,2-trifluoroethyl α-fluoroacrylate, 2,2,3,3,3-pentafluoropropyl α-fluoroacrylate, 2-(perfluorobutyl)ethyl α-fluoroacrylate, 2-(perfluorohexyl)ethyl α-fluoroacrylate, 1H,1H,3H-tetrafluoropropyl α-fluoroacrylate, and 1H,1H,5H-octafluoropentyl α-fluoroacrylate α-Fluoroacrylic acid fluoroalkyl esters such as α-fluoroacrylic acid 1H,1H,7H-dodecafluoroheptyl, α-fluoroacrylic acid 1H-1-(trifluoromethyl)trifluoroethyl, α-fluoroacrylic acid 1H,1H,3H-hexafluorobutyl, and α-fluoroacrylic acid 1,2,2,2-tetrafluoro-1-(trifluoromethyl)ethyl; α-chloroacrylic acid benzyl; and α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl.

[0030] The proportion of the monomer unit (A) in the total monomer units constituting the copolymer is not particularly limited, and can be, for example, 30 mol% or more and 70 mol% or less. In particular, the proportion of the monomer unit (A) is preferably 50 mol% or more, more preferably more than 50 mol%, even more preferably 52 mol% or more, preferably 60 mol% or less, more preferably 55 mol% or less, and even more preferably 54 mol% or less. If the proportion of the monomer unit (A) is within the above range, a fine resist pattern can be efficiently formed with high resolution.

[0031] [Monomer unit (B)] The monomer unit (B) has the following formula (II): [ka] [In formula (II), R 5 , R 6 , R 8 and R 9 are a hydrogen atom, a halogen atom, a carboxyl group, a halogenated carboxyl group, an alkyl group, or a halogenated alkyl group, and may be the same or different from each other, R 7 is a hydrogen atom, an alkyl group, or a halogenated alkyl group, p and q are integers from 0 to 5, and p+q=5; R 6 When multiple are present, they may be the same or different, and R 7 When a plurality of are present, they may be the same or different. and represented by the following formula (IV): [ka] [In formula (IV), R 5 ~R 9 and p and q are the same as in formula (II).

[0032] Here, R in formula (II) and formula (IV) 5 , R 6 , R 8and R 9 Examples of halogen atoms that can constitute the above include a chlorine atom, a fluorine atom, a bromine atom, an iodine atom, and an astatine atom. Among these, the halogen atom is preferably a fluorine atom. In addition, R in formula (II) and formula (IV) 5 , R 6 , R 8 and R 9 Examples of halogenated carboxyl groups (-C(=O)-X; X is a halogen atom) that can constitute the above formula include a chlorocarboxyl group (-C(=O)-Cl), a fluorinated carboxyl group (-C(=O)-F), and a brominated carboxyl group (-C(=O)-Br). Furthermore, R in formula (II) and formula (IV) 5 ~R 9 Examples of the alkyl group that can constitute the above group include unsubstituted alkyl groups having from 1 to 5 carbon atoms. Among these, preferred alkyl groups are methyl and ethyl groups. In addition, R in formula (II) and formula (IV) 5 ~R 9 Examples of the halogenated alkyl group that can constitute the above group include alkyl groups substituted with fluorine atoms, and perfluoroalkyl groups having 1 to 5 carbon atoms are preferred, with trifluoromethyl groups being more preferred.

[0033] From the viewpoint of easiness in preparation of the copolymer and improvement in severability of the main chain when irradiated with ionizing radiation or the like, R 5 is preferably a hydrogen atom or an alkyl group, more preferably an unsubstituted alkyl group having 1 to 5 carbon atoms, and even more preferably a methyl group.

[0034] From the viewpoint of easiness of preparation of the copolymer and improvement of scission property of the main chain when irradiated with ionizing radiation, etc., it is preferable that a plurality of R 6 and / or R 7 are all preferably a hydrogen atom or an alkyl group, more preferably a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and further preferably a hydrogen atom. From the viewpoint of easiness of preparation of the copolymer and improvement of severability of the main chain when irradiated with ionizing radiation or the like, it is preferable that p in formula (II) and formula (IV) are 5, q is 0, and there are five R 6 It is preferable that all of R are hydrogen atoms or alkyl groups. 6 It is more preferable that all of R are hydrogen atoms or unsubstituted alkyl groups having 1 to 5 carbon atoms. 6 It is more preferable that all of are hydrogen atoms.

[0035] Furthermore, from the viewpoint of easiness in preparation of the copolymer and improvement in severability of the main chain when irradiated with ionizing radiation or the like, R 8 and R 9 are each preferably a hydrogen atom or an alkyl group, more preferably a hydrogen atom or an unsubstituted alkyl group having 1 to 5 carbon atoms, and further preferably a hydrogen atom.

[0036] The monomer (b) represented by the above formula (IV) capable of forming the monomer unit (B) represented by the above formula (II) is not particularly limited, and examples thereof include α-methylstyrene and its derivatives such as the following (b-1) to (b-18).

[0037] [ka]

[0038] From the viewpoint of easiness of preparation of the copolymer and improvement of severability of the main chain when irradiated with ionizing radiation, etc., the monomer unit (B) is preferably a structural unit derived from α-methylstyrene or 4-methyl-α-methylstyrene. That is, the copolymer preferably has an α-methylstyrene unit or a 4-methyl-α-methylstyrene unit.

[0039] The proportion of the monomer unit (B) in the total monomer units constituting the copolymer is not particularly limited, and can be, for example, 30 mol% or more and 70 mol% or less. In particular, the proportion of the monomer unit (B) is preferably 40 mol% or more, more preferably 45 mol% or more, even more preferably 46 mol% or more, preferably 50 mol% or less, more preferably less than 50 mol%, and even more preferably 48 mol% or less. If the proportion of the monomer unit (B) is within the above range, a fine resist pattern can be efficiently formed with high resolution.

[0040] [Total number of fluorine atoms in monomer unit (A) and monomer unit (B)] Here, the copolymer is preferably such that the total number of fluorine atoms in one monomer unit (A) and one monomer unit (B) is 1 or more, more preferably 3 or more, and even more preferably 5 or more. It is presumed that if the total number of fluorine atoms in the monomer unit (A) and the monomer unit (B) is 1 or more, excessive entanglement between the polymer chains constituting the copolymer is suppressed, and the filter liquid permeability of the solution containing the copolymer can be improved. The upper limit of the total number of fluorine atoms in the monomer unit (A) and the monomer unit (B) is not particularly limited, but can be, for example, 6 or less.

[0041] [Properties of copolymer] The copolymer preferably has a weight average molecular weight (Mw) of more than 30,000, more preferably more than 100,000, even more preferably at least 110,000, particularly preferably at least 150,000, and preferably not more than 500,000. If the weight average molecular weight of the copolymer is more than 30,000, the clarity of the resist pattern obtained using the positive resist composition can be ensured, and if it is not more than 500,000, the filter permeability of a solution containing the copolymer can be improved.

[0042] Furthermore, the number average molecular weight (Mn) of the copolymer is preferably at least 20,000, more preferably at least 70,000, and even more preferably at least 110,000, and is preferably at most 400,000, and more preferably at most 300,000. If the number average molecular weight of the copolymer is at least 20,000, the clarity of the resist pattern obtained using the positive resist composition can be ensured, and if it is at most 400,000, the filter permeability of a solution containing the copolymer can be improved.

[0043] The molecular weight distribution (Mw / Mn) of the copolymer is preferably 1.20 or more, more preferably 1.30 or more, even more preferably 1.40 or more, particularly preferably 1.50 or more, and is preferably 2.00 or less, more preferably 1.90 or less.

[0044] In the present invention, the "weight average molecular weight" and the "number average molecular weight" can be measured using gel permeation chromatography in terms of standard polystyrene, and the "molecular weight distribution" can be determined by calculating the ratio of the weight average molecular weight to the number average molecular weight (weight average molecular weight / number average molecular weight).

[0045] [Preparation of copolymer] The copolymer having the above-mentioned monomer unit (A) and monomer unit (B) can be prepared, for example, by polymerizing a monomer composition containing the monomer (a) and the monomer (b), recovering the obtained copolymer, and optionally purifying it. The composition, molecular weight distribution, weight average molecular weight, and number average molecular weight of the copolymer can be adjusted by changing the polymerization conditions (e.g., polymerization temperature, polymerization time, and type and amount of polymerization initiator) and purification conditions. Specifically, for example, the weight average molecular weight and number average molecular weight can be increased by lowering the polymerization temperature. Also, the weight average molecular weight and number average molecular weight can be increased by shortening the polymerization time. Furthermore, the molecular weight distribution can be narrowed by performing purification.

[0046] Here, the monomer composition used for preparing the copolymer may be a mixture of monomer components including monomer (a) and monomer (b), an optional solvent, an optional polymerization initiator, and optional additives. The polymerization of the monomer composition may be carried out using a known method such as solution polymerization or emulsion polymerization. Among them, it is preferable to use cyclopentanone, water, or the like as the solvent. As the surfactant used in the emulsion polymerization, an anionic surfactant consisting of an alkali salt of a higher fatty acid, such as half-hardened beef tallow fatty acid potassium soap, can be preferably used. As the polymerization initiator used in the emulsion polymerization, a water-soluble initiator, such as potassium persulfate, can be preferably used. Furthermore, in the emulsion polymerization, a buffer, such as sodium carbonate, can be optionally used. In addition, in the emulsion polymerization, an oxidation-reduction agent, such as sodium dithionite, sodium ferric ethylenediaminetetraacetate trihydrate, tetrasodium ethylenediaminetetraacetate tetrahydrate, and sodium formaldehyde sulfoxylate can be optionally used.

[0047] The polymer obtained by polymerizing the monomer composition may be used as a copolymer as it is, but is not particularly limited thereto. It can be recovered by adding a good solvent such as tetrahydrofuran to a solution containing the polymer, and then dropping the solution to which the good solvent has been added into a poor solvent such as methanol to coagulate the polymer.

[0048] The purification method used for purifying the obtained polymer is not particularly limited, and examples thereof include known purification methods such as reprecipitation and column chromatography. Among them, the reprecipitation method is preferably used as the purification method. The purification of the polymer may be repeated several times.

[0049] The purification of the polymer by the reprecipitation method is preferably carried out, for example, by dissolving the obtained polymer in a good solvent such as tetrahydrofuran, and then dropping the obtained solution into a mixed solvent of a good solvent such as tetrahydrofuran and a poor solvent such as methanol to precipitate a part of the polymer. In this way, if the solution of the polymer is dropped into a mixed solvent of a good solvent and a poor solvent to perform purification, the molecular weight distribution, weight average molecular weight and number average molecular weight of the obtained copolymer can be easily adjusted by changing the type and mixing ratio of the good solvent and the poor solvent. Specifically, for example, the molecular weight of the copolymer precipitated in the mixed solvent can be increased by increasing the ratio of the good solvent in the mixed solvent.

[0050] In addition, when purifying a polymer by the reprecipitation method, a polymer precipitated in a mixed solvent of a good solvent and a poor solvent may be used as the copolymer as long as it satisfies the desired properties, or a polymer not precipitated in the mixed solvent (i.e., a polymer dissolved in the mixed solvent) may be used. Here, the polymer not precipitated in the mixed solvent can be recovered from the mixed solvent by a known method such as concentration to dryness.

[0051] <<Solvent>> The solvent is not particularly limited as long as it is capable of dissolving the above-mentioned copolymer, and it is possible to use known solvents such as those described in Japanese Patent No. 5938536. Among them, from the viewpoint of obtaining a positive resist composition with an appropriate viscosity and improving the coatability of the positive resist composition, it is preferable to use anisole, propylene glycol monomethyl ether acetate (PGMEA), cyclopentanone, cyclohexanone, or isoamyl acetate as the solvent.

[0052] <<Solution preparation>> The solution can be prepared by mixing the above-mentioned copolymer, the solvent, and any known additives that may be used. The mixing method is not particularly limited, and the mixing may be carried out by a known method.

[0053] <Filtration> In the method for producing a positive resist composition of the present invention, the above-mentioned solution is filtered using a filter. The filter is not particularly limited, and examples thereof include fluorocarbon, cellulose, nylon, polyester, and hydrocarbon filtration membranes. Among them, from the viewpoint of effectively preventing foreign matter such as metal from being mixed into the positive resist composition from metal piping that may be used during the preparation of the copolymer, the material constituting the filter is preferably nylon, polyethylene, polypropylene, polytetrafluoroethylene, polyfluorocarbon such as Teflon (registered trademark), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), polyimide, nylon, and a composite membrane of polyethylene and nylon. As the filter, for example, one disclosed in U.S. Pat. No. 6,103,122 may be used. In addition, filters are commercially available as Zeta Plus (registered trademark) 40Q manufactured by CUNO Incorporated, Impact (registered trademark) 8G disposable filter and Optimizer (registered trademark) AT photochemical filter manufactured by Entegris, and the like. Furthermore, the filter may contain a strong cationic or weak cationic ion exchange resin. Here, the average particle size of the ion exchange resin is not particularly limited, but is preferably 2 μm or more and 10 μm or less. Examples of the cation exchange resin include sulfonated phenol-formaldehyde condensates, sulfonated phenol-benzaldehyde condensates, sulfonated styrene-divinylbenzene copolymers, sulfonated methacrylic acid-divinylbenzene copolymers, and other types of sulfonic acid or carboxylic acid group-containing polymers. The cation exchange resin includes H + Counterion, NH4 + Counterion or alkali metal counterion, e.g. K + and Na + Counterions are provided. The cation exchange resin preferably has hydrogen counterions. Examples of such cation exchange resins include H +Sulfonated styrene-divinylbenzene copolymers with counterions include Microlite® PrCH from Purolite Corp. Such cation exchange resins are commercially available as AMBERLYST® from Rohm and Haas.

[0054] Here, the particle size of the filter must be 20 nm or less, which allows for sufficient removal of foreign matter. The particle size of the filter is not particularly limited as long as it is 20 nm or less, and may be appropriately determined in consideration of the removal of foreign matter and the filter permeability of the solution. The particle size of the filter can be appropriately set within the range of, for example, 1 nm or more and 20 nm or less, 3 nm or more and 20 nm or less, 5 nm or more and 20 nm or less, 10 nm or more and 20 nm or less, 1 nm or more and 10 nm or less, 3 nm or more and 10 nm or less, 5 nm or more and 10 nm or less, 1 nm or more and 5 nm or less, 3 nm or more and 5 nm or less, or 1 nm or more and 3 nm or less.

[0055] The filtrate obtained by passing through the above-mentioned filter can be used as a positive resist composition.

[0056] (Method of forming resist pattern) In the resist pattern forming method of the present invention, a resist pattern is formed using a positive resist composition obtained by the above-mentioned method for producing a positive resist composition of the present invention. Specifically, the resist pattern forming method of the present invention includes at least a step of forming a resist film using the positive resist composition (resist film forming step), a step of exposing the resist film (exposure step), and a step of developing the exposed resist film (development step). Note that the resist pattern forming method of the present invention may include steps (other steps) other than the above-mentioned resist film forming step, exposure step, and development step. Furthermore, the method of forming a resist pattern of the present invention uses a positive resist composition obtained by the above-mentioned method of producing a positive resist composition of the present invention, so it is possible to form a resist pattern in which the amount of foreign matter is sufficiently reduced.

[0057] <Resist film formation process> In the resist film forming step, the positive resist composition of the present invention is applied onto a workpiece such as a substrate to be processed using the resist pattern, and the applied positive resist composition is dried to form a resist film. The application method and drying method are not particularly limited, and known application methods and drying methods can be used.

[0058] <Exposure process> In the exposure step, the resist film formed in the resist film forming step is irradiated with ionizing radiation or the like to draw a desired pattern. For irradiation with ionizing radiation, etc., known lithography devices such as electron beam lithography devices and laser lithography devices can be used. For example, for irradiation with EUV, known exposure devices such as EQ-10M (manufactured by ENERGETIQ) and NXE (manufactured by ASML) can be used.

[0059] <Developing process> In the developing step, the resist film on which the pattern is drawn is brought into contact with a developer to develop the resist film, thereby forming a resist pattern on the workpiece. The method for bringing the resist film into contact with the developer is not particularly limited, and known methods such as immersing the resist film in the developer or applying the developer to the resist film can be used. The type of developer can be appropriately selected according to the properties of the copolymer described above. Specifically, when selecting a developer, it is preferable to select a developer that does not dissolve the resist film before the exposure process, but can dissolve the exposed part of the resist film after the exposure process. In addition, the developer may be used alone or in any ratio of two or more.

[0060] Examples of the developer include hydrofluorocarbons such as 1,1,1,2,3,4,4,5,5,5-decafluoropentane (CF3CFHCFHCF2CF3), 1,1,1,2,2,3,3,4,4,5,5,6,6-tridecafluorohexane, 1,1,1,2,2,3,4,5,5,5-decafluoropentane, 1,1,1,3,3-pentafluorobutane, and 1,1,1,2,2,3,3,4,4-nonafluorohexane; 2,2-dichloro-1,1,1-trifluoroethane; 1,1-dichloro-1-fluoroethane; and 1,1-dichloro-2,2,3,3,3-pentafluorohexane. hydrochlorofluorocarbons such as 1,3-dichloro-1,1,2,2,3-pentafluoropropane (CClF2CF2CHClF) and hydrochlorofluorocarbons such as methyl nonafluorobutyl ether (CF3CF2CF2CF2OCH3), methyl nonafluoroisobutyl ether, ethyl nonafluorobutyl ether (CF3CF2CF2CF2OC2H5), ethyl nonafluoroisobutyl ether, perfluorohexyl methyl ether (CF3CF2CF(OCH3)C3F7), and CF4, C2F6, C3F8, C4F8, C4F 10 , C5F 12 , C6F 12 , C6F 14 , C7F 14 , C7F 16 , C8F 18 , C9F 20 Fluorine-based solvents such as perfluorocarbons such as fluorine, ethanol, 1-propanol, 2-propanol (isopropyl alcohol), 1-butanol, 2-butanol, 1-pentanol, 2-pentanol, 3-pentanol, 1-hexanol, and other alcohols; acetates having an alkyl group such as amyl acetate and hexyl acetate; mixtures of fluorine-based solvents and alcohols; mixtures of fluorine-based solvents and acetates having an alkyl group; mixtures of alcohols and acetates having an alkyl group; and mixtures of fluorine-based solvents, alcohols, and acetates having an alkyl group.

[0061] <Other processes> Other steps optionally included in the resist pattern forming method of the present invention are not particularly limited, and examples thereof include a step of providing an inorganic or organic underlayer film on a substrate before the resist film forming step (underlayer film forming step), a step of heating the exposed resist film between the exposure step and the development step (post-exposure bake step), and a step of removing the developer by air blowing with a gas such as nitrogen and / or a rinsing treatment using a rinsing solution after the development step (developer removal step).

[0062] (Etching method) A resist pattern obtained by the above-mentioned method for forming a resist pattern can be used as a mask to etch a workpiece (for example, an underlayer film and / or a substrate), thereby forming a pattern on the workpiece. The number of etching steps is not particularly limited, and may be one or more. The etching step may be dry etching or wet etching, but dry etching is preferred. Dry etching can be performed using a known dry etching device. The etching gas used in dry etching can be appropriately selected depending on the elemental composition of the underlayer film and the substrate to be etched. Examples of the etching gas include fluorine-based gases such as CHF3, CF4, C2F6, C3F8, and SF6; chlorine-based gases such as Cl2 and BCl3; oxygen-based gases such as O2, O3, and H2O; reducing gases such as H2, NH3, CO, CO2, CH4, C2H2, C2H4, C2H6, C3H4, C3H6, C3H8, HF, HI, HBr, HCl, NO, NH3, and BCl3; and inert gases such as He, N2, and Ar. These gases may be used alone or in combination of two or more. For dry etching of inorganic underlayer films, oxygen-based gases are usually used. Furthermore, for dry etching of a substrate, a fluorine-based gas is usually used, and a mixture of a fluorine-based gas and an inert gas is preferably used.

[0063] Furthermore, if necessary, the underlayer film remaining on the substrate may be removed before or after etching the substrate. When the underlayer film is removed before etching the substrate, the underlayer film may be a patterned underlayer film or an unpatterned underlayer film.

[0064] Here, the method of removing the underlayer film includes, for example, the above-mentioned dry etching. In addition, in the case of an inorganic underlayer film, a liquid such as a basic liquid or an acid liquid, preferably a basic liquid, may be brought into contact with the underlayer film to remove the underlayer film. Here, the basic liquid is not particularly limited, and examples thereof include alkaline hydrogen peroxide and the like. The method of removing the underlayer film by wet stripping using alkaline hydrogen peroxide is not particularly limited as long as the underlayer film and alkaline hydrogen peroxide can be brought into contact with each other for a certain period of time under heating conditions, and examples thereof include a method of immersing the underlayer film in heated alkaline hydrogen peroxide, a method of spraying alkaline hydrogen peroxide on the underlayer film in a heated environment, and a method of coating the underlayer film with heated alkaline hydrogen peroxide. After performing any of these methods, the substrate is washed with water and dried to obtain a substrate from which the underlayer film has been removed. EXAMPLES

[0065] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following description, the units "%" and "parts" expressing amounts are by mass unless otherwise specified. In the examples and comparative examples, the weight average molecular weight, number average molecular weight and molecular weight distribution of the copolymer, and the proportion of each molecular weight component in the copolymer were measured by the following methods. In addition, the filter permeability and foreign matter removal when the solution was filtered to obtain a positive resist composition were evaluated by the following methods. The results are all shown in the tables below.

[0066] <Weight average molecular weight, number average molecular weight and molecular weight distribution> For each copolymer obtained in the preparation examples, the weight average molecular weight (Mw) and number average molecular weight (Mn) were measured using gel permeation chromatography, and the molecular weight distribution (Mw / Mn) was calculated. Specifically, a gel permeation chromatograph (Tosoh Corporation, HLC-8220) was used, and tetrahydrofuran was used as a developing solvent to determine the weight average molecular weight (Mw) and number average molecular weight (Mn) of the polymer in terms of standard polystyrene. Then, the molecular weight distribution (Mw / Mn) was calculated. <Proportion of each molecular weight component in the copolymer> Using gel permeation chromatography (HLC-8220, manufactured by Tosoh Corporation) and tetrahydrofuran as a developing solvent, chromatograms of each copolymer obtained in Preparation Examples were obtained. From the obtained chromatograms, the total peak area (A) and the total peak area (B) of components with molecular weights exceeding M were calculated, and the proportion of components with molecular weights exceeding M was calculated from the following formula. Percentage of components with molecular weights greater than M (%) = (B / A) x 100 (Note that M is 10,000, 20,000, 30,000, 40,000, 50,000, 60,000, 70,000, 80,000, 90,000, 100,000, 200,000, 300,000, 400,000, 500,000, 600,000, 700,000, 800,000, 900,000, 1,000,000, 1,500,000, 2,000,000, 2,500,000, 3,000,000, 3,500,000, 4,000,000, 4,500,000, or 5,000,000.) <Filter permeability - clogging> One liter of the evaluation solution was passed through the same filter repeatedly 10 times, and after the 10 passes, the filter was checked for clogging and evaluated according to the following criteria. A: There was no clogging even after 10 passes, and there were no problems with liquid passage. B: Clogging was confirmed after 10 passes, making it difficult to pass liquid through. <Filter permeability - Change in weight average molecular weight (Mw)> 1 L of the evaluation solution (weight average molecular weight of the copolymer: Mw1) was repeatedly passed through the same filter 10 times, and the weight average molecular weight (Mw2) of the copolymer contained in the obtained positive resist composition was measured. The weight average molecular weight reduction rate (%) = (Mw1 - Mw2) / Mw1 × 100 was calculated and evaluated according to the following criteria. A: Weight average molecular weight reduction rate is 3% or less B: Weight average molecular weight reduction rate of more than 3% and less than 5% C: Weight average molecular weight reduction rate is over 5% <Filter permeability - Change in solids concentration (TS)> 1 L of the evaluation solution (solid content concentration: S1%) was repeatedly passed through the same filter 10 times, and the solid content concentration (S2%) of the obtained positive resist composition was measured. The solid content reduction rate (%) = (S1-S2) / S1 x 100% was calculated, and evaluation was performed according to the following criteria. A: Reduction in solid concentration is 3% or less B: Solid content concentration reduction rate is more than 3% and less than 5% C: Solid content concentration reduction rate exceeds 5% <Foreign matter removal> 1 liter of the evaluation solution was passed once through a filter, and the number of foreign matter particles having a particle size of 0.2 μm or more contained per milliliter of the resulting positive resist composition was counted and evaluated according to the following criteria. A: The number of foreign objects is 5 or less B: More than 5 and 10 or less foreign objects C: More than 10 foreign objects

[0067] <Preparation example 1: Copolymer A-1> <<Preparation of an aqueous solution of partially hardened beef tallow fatty acid potassium soap>> 100g of ion-exchanged water was prepared, heated to 70°C while stirring, and 8.40g of potassium hydroxide (49% aqueous solution) was added. Next, 19.6g of beef tallow 45° hardened fatty acid HFA (NOF Corp.) was added at a rate of 1.28g / min, and then 0.126g of potassium silicate was added. The mixture was stirred at 80°C for more than 2 hours to obtain an aqueous solution of semi-hardened beef tallow fatty acid potassium soap with a solid content of 18%. <<Synthesis of Polymers>> In a glass ampoule containing a stirrer, 3.000 g of methyl α-chloroacrylate as monomer (a) and 8.656 g of 4-fluoro-α-methylstyrene as monomer (b) were added. In addition, 0.5463 g of the aqueous solution of the semi-hardened beef tallow fatty acid potassium soap with a solid content of 18% prepared above, 6.771 g of ion-exchanged water, and 0.0027 g of sodium dithionite, 0.0010 g of sodium ferric ethylenediaminetetraacetate trihydrate, 0.0025 g of tetrasodium ethylenediaminetetraacetate tetrahydrate, and 0.0015 g of sodium aldehyde sulfoxylate were added to the same ampoule to prepare a monomer composition, and the ampoule was sealed and pressurized and depressurized with nitrogen gas 10 times to remove oxygen from the system. The system was then cooled to 5°C and the polymerization reaction was carried out for 48 hours. Next, 10 g of tetrahydrofuran (THF) was added to the system, and the resulting solution was dropped into 400 g of methanol (MeOH) to precipitate a polymer. The precipitated polymer (copolymer A-1) was then collected by filtration. The resulting copolymer A-1 was a copolymer containing 50 mol % each of α-chloromethyl acrylate units (ACAM units) and 4-fluoro-α-methylstyrene units (FAMS units) (m:n in the formula below=50:50). [ka]

[0068] <Preparation example 2: Copolymer A-2> <<Preparation of aqueous solution and polymer of partially hardened beef tallow fatty acid potassium soap>> In the same manner as in Preparation Example 1, an aqueous solution of semi-hardened beef tallow fatty acid potassium soap with a solid content of 18% and a polymer were prepared. <<Purification of polymer>> The polymer recovered by filtration was dissolved in 10 g of THF, and the resulting solution was added dropwise to 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 66:34) to precipitate a coagulant. The solution containing the precipitated coagulant was then filtered using a Kiriyama funnel to obtain a copolymer A-2 containing 50 mol% each of ACAM units and FAMS units.

[0069] <Preparation Example 3: Copolymer B-3> <<Preparation of an aqueous solution of partially hardened beef tallow fatty acid potassium soap>> In the same manner as in Preparation Example 1, an aqueous solution of semi-hardened beef tallow fatty acid potassium soap having a solid content of 18% was prepared. <<Synthesis of Polymers>> In a glass ampoule containing a stirrer, 3.000 g of 2,2,2-trifluoroethyl α-chloroacrylate as monomer (a) and 4.785 g of α-methylstyrene as monomer (b) were added. Furthermore, 0.5463 g of the aqueous solution of the semi-hardened beef tallow fatty acid potassium soap with a solid content of 18% prepared above and 6.771 g of ion-exchanged water were added to the same ampoule to prepare a monomer composition, and the ampoule was sealed and pressurized and depressurized with nitrogen gas 10 times to remove oxygen from the system. The system was heated to 70°C and polymerization reaction was carried out for 6 hours. Next, 10 g of THF was added to the system, and the resulting solution was dropped into 400 g of MeOH to precipitate a polymer. The precipitated polymer was then collected by filtration. The obtained polymer was a copolymer containing 50 mol % each of 2,2,2-trifluoroethyl α-chloroacrylate units (ACATFE units) and α-methylstyrene (AMS units) (m:n in the following formula = 50:50). [ka] <<Purification of polymer>> The polymer recovered by filtration was dissolved in 10 g of THF, and the resulting solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 30:70) to precipitate a coagulant. The solution containing the precipitated coagulant was then filtered using a Kiriyama funnel to obtain a copolymer B-3 containing 50 mol% each of ACATFE units and AMS units.

[0070] <Preparation example 4: Copolymer B-4> In the synthesis of the polymer, the temperature of the polymerization reaction was changed to 60°C, and in the purification of the polymer, the solvent ratio of the mixed solvent of THF and MeOH was changed to THF:MeOH (mass ratio) = 32:68. Except for this, the same operations as in Preparation Example 3 were carried out to obtain a copolymer B-4 containing 50 mol% each of ACATFE units and AMS units.

[0071] <Preparation Example 5: Copolymer B-5> In the synthesis of the polymer, the temperature of the polymerization reaction was changed to 50°C, and in the purification of the polymer, the solvent ratio of the mixed solvent of THF and MeOH was changed to THF:MeOH (mass ratio) = 33:67. Except for this, the same operations as in Preparation Example 3 were carried out to obtain a copolymer B-5 containing 50 mol% each of ACATFE units and AMS units.

[0072] <Preparation Example 6: Copolymer B-6> In the synthesis of the polymer, the polymerization reaction time was changed to 11 hours and the temperature to 40°C, and in the purification of the polymer, the solvent ratio of the mixed solvent of THF and MeOH was changed to THF:MeOH (mass ratio) = 34:66. Except for this, the same operations as in Preparation Example 3 were carried out to obtain a copolymer B-6 containing 50 mol% each of ACATFE units and AMS units.

[0073] <Preparation Example 7: Copolymer C-7> <<Preparation of an aqueous solution of partially hardened beef tallow fatty acid potassium soap>> In the same manner as in Preparation Example 1, an aqueous solution of semi-hardened beef tallow fatty acid potassium soap having a solid content of 18% was prepared. <<Synthesis of Polymers>> In a glass ampoule containing a stirrer, 3.000 g of 2,2,2-trifluoroethyl α-chloroacrylate as monomer (a) and 5.525 g of 4-fluoro-α-methylstyrene as monomer (b) were added. In addition, 0.5463 g of the aqueous solution of the semi-hardened beef tallow fatty acid potassium soap with a solid content of 18% prepared above and 6.771 g of ion-exchanged water were added to the same ampoule to prepare a monomer composition, and the ampoule was sealed and pressurized and depressurized with nitrogen gas 10 times to remove oxygen from the system. The system was heated to 70°C and polymerization reaction was carried out for 6 hours. Next, 10 g of THF was added to the system, and the resulting solution was dropped into 400 g of MeOH to precipitate a polymer. The precipitated polymer was then collected by filtration. The obtained polymer was a copolymer containing 50 mol % each of 2,2,2-trifluoroethyl α-chloroacrylate units (ACATFE units) and 4-fluoro-α-methylstyrene (FAMS units) (m:n in the formula below = 50:50). [ka] <<Purification of polymer>> The polymer recovered by filtration was dissolved in 10 g of THF, and the resulting solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 28:72) to precipitate a coagulant. The solution containing the precipitated coagulant was then filtered using a Kiriyama funnel to obtain copolymer C-7 containing 50 mol% each of ACATFE units and FAMS units.

[0074] <Preparation Example 8: Copolymer C-8> In the synthesis of the polymer, the temperature of the polymerization reaction was changed to 60°C, and in the purification of the polymer, the solvent ratio of the mixed solvent of THF and MeOH was changed to THF:MeOH (mass ratio) = 30:70. Except for this, the same operations as in Preparation Example 7 were carried out to obtain a copolymer C-8 containing 50 mol% each of ACATFE units and FAMS units.

[0075] <Preparation Example 9: Copolymer C-9> In the synthesis of the polymer, the temperature of the polymerization reaction was changed to 50°C, and in the purification of the polymer, the solvent ratio of the mixed solvent of THF and MeOH was changed to THF:MeOH (mass ratio) = 31:69. Except for this, the same operations as in Preparation Example 7 were carried out to obtain a copolymer C-9 containing 50 mol% each of ACATFE units and FAMS units.

[0076] <Preparation Example 10: Copolymer C-10> In the synthesis of the polymer, the polymerization reaction time was changed to 11 hours and the temperature to 40°C, and in the purification of the polymer, the solvent ratio of the mixed solvent of THF and MeOH was changed to THF:MeOH (mass ratio) = 33:67. Except for this, the same operations as in Preparation Example 7 were carried out to obtain a copolymer C-10 containing 50 mol% each of ACATFE units and FAMS units.

[0077] <Preparation Example 11: Copolymer D-11> <<Synthesis of Polymers>> A monomer composition containing 3.000 g of α-chloroacrylic acid 2,2,3,3,3-pentafluoropropyl as monomer (a) and 3.476 g of α-methylstyrene as monomer (b), 1.620 g of cyclopentanone as a solvent, and 0.005512 g of azobisisobutyronitrile as a polymerization initiator was placed in a glass container, the glass container was sealed and replaced with nitrogen, and the polymerization reaction was carried out by stirring for 6 hours in a constant temperature bath at 78 ° C. under a nitrogen atmosphere. After that, the temperature was returned to room temperature, the glass container was opened to the atmosphere, and then 10 g of THF was added to the obtained solution. Then, the solution to which THF was added was dropped into 300 g of MeOH to precipitate a polymer. Then, the precipitated polymer was collected by filtration. The obtained polymer was a copolymer containing 50 mol % each of α-chloroacrylic acid 2,2,3,3,3-pentafluoropropyl units (ACAPFP units) and α-methylstyrene (AMS units) (m:n in the following formula = 50:50). [ka] <<Purification of polymer>> The polymer recovered by filtration was dissolved in 10 g of THF, and the resulting solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 15:85) to precipitate a coagulant. The solution containing the precipitated coagulant was then filtered using a Kiriyama funnel to obtain a copolymer D-11 containing 50 mol% each of ACAPFP units and AMS units.

[0078] <Preparation Example 12: Copolymer D-12> The amount of α-methylstyrene as monomer (b) was changed to 3.283 g, the amount of cyclopentanone as a solvent was changed to 1.571 g, the amount of azobisisobutyronitrile as a polymerization initiator was changed to 0.0005207 g, and the polymerization reaction time was changed to 2 hours, but the polymerization reaction was carried out in the same manner as in Preparation Example 11. After that, the temperature was returned to room temperature, the glass container was opened to the air, and then 10 g of THF was added to the obtained solution. Then, the solution to which THF was added was dropped into 300 g of MeOH to precipitate a polymer. Then, the precipitated polymer was collected by filtration. Furthermore, the polymer collected by filtration was dissolved in 10 g of THF, and the solution obtained by adding THF was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 21:79) to precipitate a polymer. Then, the precipitated polymer was collected by filtration. The obtained polymer was designated as copolymer D-12 containing 50 mol % each of ACAPFP units and AMS units.

[0079] <Preparation Example 13: Copolymer D-13> The amount of α-methylstyrene as monomer (b) was changed to 3.468 g, the amount of cyclopentanone as a solvent was changed to 6.466 g, the amount of azobisisobutyronitrile as a polymerization initiator was changed to 0.002065 g, and the polymerization reaction temperature was changed to 53 ° C., and the time was changed to 50 hours, but the polymerization reaction was carried out in the same manner as in Preparation Example 11. After that, the temperature was returned to room temperature, the glass container was opened to the air, and then 10 g of THF was added to the obtained solution. Then, the solution to which THF was added was dropped into 300 g of MeOH to precipitate a polymer. Then, the precipitated polymer was collected by filtration. Furthermore, the polymer collected by filtration was dissolved in 10 g of THF, and the solution obtained by adding THF was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 24:76) to precipitate a polymer. Then, the precipitated polymer was collected by filtration. The obtained polymer was designated as copolymer D-13 containing 50 mol % each of ACAPFP units and AMS units.

[0080] <Preparation Example 14: Copolymer D-14> The amount of α-methylstyrene as monomer (b) was changed to 3.468 g, the amount of cyclopentanone as a solvent was changed to 6.467 g, the amount of azobisisobutyronitrile as a polymerization initiator was changed to 0.001377 g, and the polymerization reaction temperature was changed to 40 ° C., and the time was changed to 50 hours, but the polymerization reaction was carried out in the same manner as in Preparation Example 11. After that, the temperature was returned to room temperature, the glass container was opened to the air, and then 10 g of THF was added to the obtained solution. Then, the solution to which THF was added was dropped into 300 g of MeOH to precipitate a polymer. Then, the precipitated polymer was collected by filtration. Furthermore, the polymer collected by filtration was dissolved in 10 g of THF, and the solution obtained by adding THF was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 26:74) to precipitate a polymer. Then, the precipitated polymer was collected by filtration. The obtained polymer was designated as copolymer D-14 containing 50 mol % each of ACAPFP units and AMS units.

[0081] <Preparation Example 15: Copolymer D-15> <<Preparation of an aqueous solution of partially hardened beef tallow fatty acid potassium soap>> In the same manner as in Preparation Example 1, an aqueous solution of semi-hardened beef tallow fatty acid potassium soap having a solid content of 18% was prepared. <<Synthesis of Polymers>> 3.000 g of 2,2,3,3,3-pentafluoropropyl α-chloroacrylate as monomer (a) and 3.782 g of α-methylstyrene as monomer (b) were added to a glass ampoule containing a stirrer. Furthermore, 0.5463 g of the aqueous solution of the semi-hardened beef tallow fatty acid potassium soap with a solid content of 18% prepared above and 6.771 g of ion-exchanged water were added to the same ampoule to prepare a monomer composition, and the ampoule was sealed and pressurized and depressurized with nitrogen gas 10 times to remove oxygen from the system. The system was heated to 70°C and polymerization reaction was carried out for 6 hours. Next, 10 g of THF was added to the system, and the resulting solution was dropped into 400 g of MeOH to precipitate a polymer. The precipitated polymer was then collected by filtration. The obtained polymer was a copolymer containing 50 mol % each of ACAPFP units and AMS units. <<Purification of polymer>> The polymer recovered by filtration was dissolved in 10 g of THF, and the resulting solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 29:71) to precipitate a coagulant. The solution containing the precipitated coagulant was then filtered using a Kiriyama funnel to obtain a copolymer D-15 containing 50 mol% each of ACAPFP units and AMS units.

[0082] <Preparation Example 16: Copolymer D-16> The same operations as in Preparation Example 15 were carried out except that the temperature of the polymerization reaction was changed to 60°C during the synthesis of the polymer, and the solvent ratio of the mixed solvent of THF and MeOH was changed to THF:MeOH (mass ratio) = 31:69 during the purification of the polymer, to obtain a copolymer D-16 containing 50 mol% each of ACAPFP units and AMS units.

[0083] <Preparation Example 17: Copolymer D-17> The same operations as in Preparation Example 15 were carried out except that the temperature of the polymerization reaction was changed to 50°C during the synthesis of the polymer, and the solvent ratio of the mixed solvent of THF and MeOH was changed to THF:MeOH (mass ratio) = 32:68 during the purification of the polymer, to obtain a copolymer D-17 containing 50 mol% each of ACAPFP units and AMS units.

[0084] <Preparation Example 18: Copolymer D-18> In the synthesis of the polymer, the polymerization reaction time was changed to 11 hours and the temperature to 40°C, and in the purification of the polymer, the solvent ratio of the mixed solvent of THF and MeOH was changed to THF:MeOH (mass ratio) = 34:66. Except for this, the same operations as in Preparation Example 15 were carried out to obtain a copolymer D-18 containing 50 mol% each of ACAPFP units and AMS units.

[0085] <Preparation Example 19: Copolymer E-19> <<Synthesis of Polymers>> A monomer composition containing 3.000 g of α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl as monomer (a), 2.493 g of α-methylstyrene as monomer (b), and 0.003953 g of azobisisobutyronitrile as a polymerization initiator was placed in a glass container, the glass container was sealed and replaced with nitrogen, and the polymerization reaction was carried out by stirring for 3.5 hours in a thermostatic bath at 78°C under a nitrogen atmosphere. After that, the temperature was returned to room temperature, the glass container was opened to the atmosphere, and then 10 g of THF was added to the obtained solution. Then, the solution to which THF was added was dropped into 300 g of MeOH to precipitate a polymer. Then, the precipitated polymer was collected by filtration. The obtained polymer was a copolymer containing 50 mol% each of α-chloroacrylate-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units (ACAFPh units) and α-methylstyrene (AMS units) (m:n in the formula below = 50:50). [ka] <<Purification of polymer>> The polymer recovered by filtration was dissolved in 10 g of THF, and the resulting solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 20:80) to precipitate a coagulant. The solution containing the precipitated coagulant was then filtered using a Kiriyama funnel to obtain a copolymer E-19 containing 50 mol% each of ACAFPh units and AMS units.

[0086] <Preparation Example 20: Copolymer E-20> <<Synthesis of Polymers>> In the synthesis of the polymer, 2.833 g of cyclopentanone as a solvent was placed in a glass container instead of azobisisobutyronitrile as a polymerization initiator, and the polymerization reaction was carried out in the same manner as in Preparation Example 19, except that the reaction temperature was changed to 50°C and the reaction time was changed to 25 hours, and the polymer was recovered by filtration. The obtained polymer was a copolymer containing 50 mol% each of ACAFPh units and AMS units. <<Purification of polymer>> The polymer recovered by filtration was dissolved in 10 g of THF, and the resulting solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 27:73) to precipitate a coagulant. The solution containing the precipitated coagulant was then filtered using a Kiriyama funnel to obtain a copolymer E-20 containing 50 mol% each of ACAFPh units and AMS units.

[0087] <Preparation Example 21: Copolymer E-21> <<Synthesis of Polymers>> In the synthesis of the polymer, 2.833 g of cyclopentanone as a solvent was placed in a glass container instead of azobisisobutyronitrile as a polymerization initiator, and the polymerization reaction was carried out in the same manner as in Preparation Example 19, except that the reaction temperature was changed to 30°C and the reaction time was changed to 80 hours, and the polymer was recovered by filtration. The obtained polymer was a copolymer containing 50 mol% each of ACAFPh units and AMS units. <<Purification of polymer>> The polymer recovered by filtration was dissolved in 10 g of THF, and the resulting solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 29:71) to precipitate a coagulant. The solution containing the precipitated coagulant was then filtered using a Kiriyama funnel to obtain a copolymer E-21 containing 50 mol% each of ACAFPh units and AMS units.

[0088] <Preparation Example 22: Copolymer E-22> <<Preparation of an aqueous solution of partially hardened beef tallow fatty acid potassium soap>> In the same manner as in Preparation Example 1, an aqueous solution of semi-hardened beef tallow fatty acid potassium soap having a solid content of 18% was prepared. <<Synthesis of Polymers>> In a glass ampoule containing a stirrer, 3.000 g of α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl as monomer (a) and 2.712 g of α-methylstyrene as monomer (b) were added. Furthermore, 0.5463 g of the aqueous solution of the semi-hardened beef tallow fatty acid potassium soap with a solid content of 18% prepared above and 6.771 g of ion-exchanged water were added to the same ampoule to prepare a monomer composition, and the ampoule was sealed and pressurized and depressurized with nitrogen gas 10 times to remove oxygen from the system. The system was heated to 40°C and polymerization reaction was carried out for 11 hours. Next, 10 g of THF was added to the system, and the resulting solution was dropped into 400 g of MeOH to precipitate a polymer. The precipitated polymer was then collected by filtration. The obtained polymer was a copolymer containing 50 mol % each of ACAFPh units and AMS units. <<Purification of polymer>> The polymer recovered by filtration was dissolved in 10 g of THF, and the resulting solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 35:65) to precipitate a coagulant. The solution containing the precipitated coagulant was then filtered using a Kiriyama funnel to obtain a copolymer E-22 containing 50 mol% each of ACAFPh units and AMS units.

[0089] <Preparation Example 23: Copolymer E-23> <<Synthesis of Polymers>> In the synthesis of the polymer, the amount of α-methylstyrene as monomer (b) was changed to 1.066 g, 1.743 g of cyclopentanone as a solvent was placed in the glass container instead of azobisisobutyronitrile as a polymerization initiator, the reaction temperature was changed to 30°C, and the reaction time was changed to 50 hours, but other than these, the polymerization reaction was carried out in the same manner as in Preparation Example 19, and the polymer was recovered by filtration. The obtained polymer was a copolymer containing 54 mol % of ACAFPh units and 46 mol % of AMS units. <<Purification of polymer>> The polymer recovered by filtration was dissolved in 10 g of THF, and the resulting solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 30:70) to precipitate a coagulant. The solution containing the precipitated coagulant was then filtered using a Kiriyama funnel to obtain a copolymer E-23 containing 54 mol% of ACAFPh units and 46 mol% of AMS units.

[0090] <Preparation Example 24: Copolymer E-24> <<Synthesis of Polymers>> In the synthesis of the polymer, the amount of α-methylstyrene as monomer (b) was changed to 1.066 g, and the polymerization reaction temperature was changed to 70°C, and the time was changed to 6 hours, but the polymerization reaction was carried out in the same manner as in Preparation Example 22, and the polymer was recovered by filtration. The obtained polymer was a copolymer containing 54 mol % of ACAFPh units and 46 mol % of AMS units. <<Purification of polymer>> The polymer recovered by filtration was dissolved in 10 g of THF, and the resulting solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 30:70) to precipitate a coagulant. The solution containing the precipitated coagulant was then filtered using a Kiriyama funnel to obtain a copolymer E-24 containing 54 mol% of ACAFPh units and 46 mol% of AMS units.

[0091] <Preparation Example 25: Copolymer E-25> The same operations as in Preparation Example 24 were carried out except that the temperature of the polymerization reaction was changed to 60°C during the synthesis of the polymer, and the solvent ratio of the mixed solvent of THF and MeOH was changed to THF:MeOH (mass ratio) = 32:68 during the purification of the polymer, thereby obtaining a copolymer E-25 containing 54 mol% of ACAFPh units and 46 mol% of AMS units.

[0092] <Preparation Example 26: Copolymer E-26> The same operations as in Preparation Example 24 were carried out except that the temperature of the polymerization reaction was changed to 50°C during the synthesis of the polymer, and the solvent ratio of the mixed solvent of THF and MeOH was changed to THF:MeOH (mass ratio) = 34:66 during the purification of the polymer, thereby obtaining a copolymer E-26 containing 54 mol% of ACAFPh units and 46 mol% of AMS units.

[0093] <Preparation Example 27: Copolymer E-27> The same operations as in Preparation Example 24 were carried out except that the polymerization reaction time was changed to 11 hours and the temperature to 40°C when synthesizing the polymer, and the solvent ratio of the mixed solvent of THF and MeOH was changed to THF:MeOH (mass ratio) = 34:66 when purifying the polymer, to obtain a copolymer E-27 containing 54 mol% of ACAFPh units and 46 mol% of AMS units.

[0094] <Preparation Example 28: Copolymer E-28> <<Preparation of an aqueous solution of partially hardened beef tallow fatty acid potassium soap>> In the same manner as in Preparation Example 1, an aqueous solution of semi-hardened beef tallow fatty acid potassium soap having a solid content of 18% was prepared. <<Synthesis of Polymers>> In a glass ampoule containing a stirrer, 3.000 g of α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl as monomer (a) and 1.066 g of α-methylstyrene as monomer (b) were added. In addition, 0.5463 g of the aqueous solution of the semi-hardened beef tallow fatty acid potassium soap with a solid content of 18% prepared above and 6.771 g of ion-exchanged water were added to the same ampoule to prepare a monomer composition, and the ampoule was sealed and pressurized and depressurized with nitrogen gas 10 times to remove oxygen from the system. The system was then heated to 75°C and polymerization reaction was carried out for 1 hour. Next, 10 g of THF was added to the system, and the resulting solution was dropped into 400 g of MeOH to precipitate a polymer. The precipitated polymer (copolymer E-28) was then collected by filtration. The resulting copolymer E-28 contained 54 mol % of ACAFPh units and 46 mol % of AMS units.

[0095] <Preparation Example 29: Copolymer E-29> <<Preparation of aqueous solution and polymer of partially hardened beef tallow fatty acid potassium soap>> In the same manner as in Preparation Example 28, an aqueous solution of semi-hardened beef tallow fatty acid potassium soap with a solid content of 18% and a polymer were prepared. <<Purification of polymer>> The polymer recovered by filtration was dissolved in 10 g of THF, and the resulting solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 30:70) to precipitate a coagulant. The solution containing the precipitated coagulant was then filtered using a Kiriyama funnel to obtain a copolymer E-29 containing 54 mol% of ACAFPh units and 46 mol% of AMS units.

[0096] <Preparation Example 30: Copolymer E-30> The copolymer E-29 obtained by the same procedure as in Preparation Example 29 was dissolved again in 10 g of THF, and the obtained solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 30:70) to precipitate a coagulant. Thereafter, the solution containing the precipitated coagulant was filtered using a Kiriyama funnel to obtain a copolymer E-30 containing 54 mol% of ACAFPh units and 46 mol% of AMS units.

[0097] <Preparation Example 31: Copolymer E-31> The copolymer E-29 obtained by the same procedure as in Preparation Example 29 was dissolved again in 10 g of THF, and the obtained solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 31:69) to precipitate a coagulant. Thereafter, the solution containing the precipitated coagulant was filtered using a Kiriyama funnel to obtain a copolymer E-31 containing 54 mol% of ACAFPh units and 46 mol% of AMS units.

[0098] <Preparation Example 32: Copolymer E-32> The copolymer E-29 obtained by the same procedure as in Preparation Example 29 was dissolved again in 10 g of THF, and the obtained solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 32:68) to precipitate a coagulant. Thereafter, the solution containing the precipitated coagulant was filtered using a Kiriyama funnel to obtain a copolymer E-32 containing 54 mol% of ACAFPh units and 46 mol% of AMS units.

[0099] <Preparation Example 33: Copolymer E-33> The copolymer E-29 obtained by the same procedure as in Preparation Example 29 was dissolved again in 10 g of THF, and the obtained solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 33:67) to precipitate a coagulant. Thereafter, the solution containing the precipitated coagulant was filtered using a Kiriyama funnel to obtain a copolymer E-33 containing 54 mol% of ACAFPh units and 46 mol% of AMS units.

[0100] <Preparation Example 34: Copolymer E-34> The copolymer E-29 obtained by the same procedure as in Preparation Example 29 was dissolved again in 10 g of THF, and the obtained solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 34:66) to precipitate a coagulant. Thereafter, the solution containing the precipitated coagulant was filtered using a Kiriyama funnel to obtain a copolymer E-34 containing 54 mol% of ACAFPh units and 46 mol% of AMS units.

[0101] <Preparation Example 35: Copolymer E-35> The copolymer E-33 obtained by the same procedure as in Preparation Example 33 was dissolved again in 10 g of THF, and the obtained solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 33:67) to precipitate a coagulant. Thereafter, the solution containing the precipitated coagulant was filtered using a Kiriyama funnel to obtain a copolymer E-35 containing 54 mol% of ACAFPh units and 46 mol% of AMS units.

[0102] <Preparation Example 36: Copolymer F-36> <<Preparation of an aqueous solution of partially hardened beef tallow fatty acid potassium soap>> In the same manner as in Preparation Example 1, an aqueous solution of semi-hardened beef tallow fatty acid potassium soap having a solid content of 18% was prepared. <<Synthesis of Polymers>> In a glass ampoule containing a stirrer, 3.000 g of α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl as monomer (a) and 3.034 g of 4-isopropenyltoluene as monomer (b) were added. In addition, 0.5463 g of the aqueous solution of the semi-hardened beef tallow fatty acid potassium soap with a solid content of 18% prepared above and 6.771 g of ion-exchanged water were added to the same ampoule to prepare a monomer composition, and the ampoule was sealed and pressurized and depressurized with nitrogen gas 10 times to remove oxygen from the system. The system was heated to 50°C and polymerization reaction was carried out for 6 hours. Next, 10 g of THF was added to the system, and the resulting solution was dropped into 400 g of MeOH to precipitate a polymer. The precipitated polymer was then collected by filtration. The obtained polymer was a copolymer containing 50 mol% each of α-chloroacrylate-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl units (ACAFPh units) and 4-isopropenyltoluene (IPT units) (m:n in the formula below = 50:50). [ka] <<Purification of polymer>> The polymer recovered by filtration was dissolved in 10 g of THF, and the resulting solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 30:70) to precipitate a coagulant. The solution containing the precipitated coagulant was then filtered using a Kiriyama funnel to obtain a copolymer F-36 containing 50 mol% each of ACAFPh units and IPT units.

[0103] <Preparation Example 37: Copolymer F-37> <<Preparation of an aqueous solution of partially hardened beef tallow fatty acid potassium soap>> In the same manner as in Preparation Example 1, an aqueous solution of semi-hardened beef tallow fatty acid potassium soap having a solid content of 18% was prepared. <<Synthesis of Polymers>> In a glass ampoule containing a stirrer, 3.000 g of α-chloroacrylic acid-1-phenyl-1-trifluoromethyl-2,2,2-trifluoroethyl as monomer (a) and 3.034 g of 4-isopropenyltoluene as monomer (b) were added. In addition, 0.5463 g of the aqueous solution of the semi-hardened beef tallow fatty acid potassium soap with a solid content of 18% prepared above and 6.771 g of ion-exchanged water were added to the same ampoule to prepare a monomer composition, and the ampoule was sealed and pressurized and depressurized with nitrogen gas 10 times to remove oxygen from the system. The system was heated to 40°C and polymerization reaction was carried out for 11 hours. Next, 10 g of THF was added to the system, and the resulting solution was dropped into 400 g of MeOH to precipitate a polymer. The precipitated polymer was then collected by filtration. The obtained polymer was a copolymer containing 50 mol % each of ACAFPh units and IPT units. <<Purification of polymer>> The polymer recovered by filtration was dissolved in 10 g of THF, and the resulting solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 33:67) to precipitate a coagulant. The solution containing the precipitated coagulant was then filtered using a Kiriyama funnel to obtain a copolymer F-37 containing 50 mol% each of ACAFPh units and IPT units.

[0104] <Preparation Example 38: Copolymer G-38> <<Synthesis of Polymers>> A monomer composition containing 3.000 g of methyl α-chloroacrylate as monomer (a) and 6.880 g of α-methylstyrene as monomer (b), 2.473 g of cyclopentanone as a solvent, and 0.01091 g of azobisisobutyronitrile as a polymerization initiator was placed in a glass container, the glass container was sealed and replaced with nitrogen, and the polymerization reaction was carried out by stirring for 48 hours in a constant temperature bath at 75°C under a nitrogen atmosphere. After that, the temperature was returned to room temperature, the glass container was opened to the air, and then 10 g of THF was added to the obtained solution. Then, the solution to which THF was added was dropped into 300 g of MeOH to precipitate a polymer. Then, the precipitated polymer was collected by filtration. The obtained polymer was a copolymer containing 50 mol % each of α-chloroacrylic acid methyl acrylate units (ACAM units) and α-methylstyrene units (AMS units) (m:n in the following formula = 50:50). [ka] <<Purification of polymer>> The polymer recovered by filtration was dissolved in 10 g of THF, and the resulting solution was added dropwise to 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 60:40) to precipitate a coagulant. The solution containing the precipitated coagulant was then filtered using a Kiriyama funnel to obtain a copolymer G-38 containing 50 mol% each of ACAM units and AMS units.

[0105] <Preparation Example 39: Copolymer G-39> <<Synthesis of Polymers>> A monomer composition containing 3.000 g of methyl α-chloroacrylate as monomer (a), 6.880 g of α-methylstyrene as monomer (b), and 0.008182 g of azobisisobutyronitrile as a polymerization initiator was placed in a glass container, the glass container was sealed and replaced with nitrogen, and the polymerization reaction was carried out by stirring for 8 hours in a constant temperature bath at 78°C under a nitrogen atmosphere. After that, the temperature was returned to room temperature, the glass container was opened to the air, and then 10 g of THF was added to the obtained solution. Then, the solution to which THF was added was dropped into 300 g of MeOH to precipitate a polymer. Then, the precipitated polymer was collected by filtration. The obtained polymer was a copolymer containing 50 mol % each of ACAM units and AMS units. <<Purification of polymer>> The polymer recovered by filtration was dissolved in 10 g of THF, and the resulting solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 63.5:36.5) to precipitate a coagulant. The solution containing the precipitated coagulant was then filtered using a Kiriyama funnel to obtain a copolymer G-39 containing 50 mol% each of ACAM units and AMS units.

[0106] <Preparation Example 40: Copolymer G-40> The same procedure as in Preparation Example 39 was carried out to purify the polymer, except that the solvent ratio of the mixed solvent of THF and MeOH was changed to THF:MeOH (mass ratio) = 65.5:34.5, to obtain a copolymer G-40 containing 50 mol% each of ACAM units and AMS units.

[0107] <Preparation Example 41: Copolymer G-41> The same procedure as in Preparation Example 39 was carried out except that the solvent ratio of the mixed solvent of THF and MeOH was changed to THF:MeOH (mass ratio) = 66:34 when purifying the polymer, thereby obtaining a copolymer G-41 containing 50 mol% each of ACAM units and AMS units.

[0108] <Preparation Example 42: Copolymer G-42> <<Preparation of an aqueous solution of partially hardened beef tallow fatty acid potassium soap>> In the same manner as in Preparation Example 1, an aqueous solution of semi-hardened beef tallow fatty acid potassium soap having a solid content of 18% was prepared. <<Synthesis of Polymers>> In a glass ampoule containing a stirrer, 3.000 g of methyl α-chloroacrylate as monomer (a) and 7.227 g of α-methylstyrene as monomer (b) were added. In addition, 0.5463 g of the aqueous solution of the semi-hardened beef tallow fatty acid potassium soap with a solid content of 18% prepared above, 6.771 g of ion-exchanged water, 0.00524 g of cumene hydroperoxide as a polymerization initiator, 0.0027 g of sodium dithionite as an oxidation-reduction agent, 0.0010 g of sodium ferric ethylenediaminetetraacetate trihydrate, 0.0025 g of tetrasodium ethylenediaminetetraacetate tetrahydrate, and 0.0015 g of sodium aldehyde sulfoxylate were added to the same ampoule to prepare a monomer composition, and then the ampoule was sealed and pressurized and depressurized with nitrogen gas 10 times to remove oxygen from the system. The system was cooled to 5°C and the polymerization reaction was carried out for 48 hours. Next, 10 g of THF was added to the system, and the resulting solution was dropped into 400 g of MeOH to precipitate the polymer. The precipitated polymer (copolymer F-42) was then collected by filtration. The resulting copolymer G-42 was a copolymer containing 50 mol % each of ACAM units and AMS units.

[0109] <Preparation Example 43: Copolymer G-43> <<Preparation of aqueous solution and polymer of partially hardened beef tallow fatty acid potassium soap>> In the same manner as in Preparation Example 1, an aqueous solution of semi-hardened beef tallow fatty acid potassium soap with a solid content of 18% and a polymer were prepared. <<Purification of polymer>> The polymer recovered by filtration was dissolved in 10 g of THF, and the resulting solution was dropped into 100 g of a mixed solvent of THF and MeOH (THF:MeOH (mass ratio) = 68.5:31.5) to precipitate a coagulant. The solution containing the precipitated coagulant was then filtered using a Kiriyama funnel to obtain a copolymer G-43 containing 50 mol% each of ACAM units and AMS units.

[0110] (Examples 1 to 2, 5 to 6, 9 to 10, 18, 22, 37, 40 to 43) The copolymers obtained in Preparation Examples 1-2, 5-6, 9-10, 18, 22, 37, and 40-41 were each dissolved in isoamyl acetate as a solvent to obtain a solution for evaluation (copolymer concentration: 1% by mass). The obtained solution for evaluation was filtered by passing it through a filter with a particle size of 20 nm (Entegris, Impact (registered trademark) 8G disposable filter. Material: UPE (ultra-high molecular weight polyethylene)), and various evaluations were performed. Note that for Examples 42 and 43, only evaluations of "filter liquid permeability - clogging" and "foreign matter removal" were performed.

[0111] (Examples 4, 8, 17, 27, 36, and 39) Each of the copolymers obtained in Preparation Examples 4, 8, 17, 27, 36, and 39 was dissolved in isoamyl acetate as a solvent to obtain a solution for evaluation (copolymer concentration: 1% by mass). The obtained solution for evaluation was filtered through a filter with a particle removal diameter of 20 nm (Impact (registered trademark) 8G disposable filter, manufactured by Entegris; material: UPE (ultra-high molecular weight polyethylene)), and various evaluations were performed. The obtained evaluation solution was filtered through a filter with a particle size of 10 nm (Impact (registered trademark) 8G disposable filter, manufactured by Entegris; material: UPE (ultra-high molecular weight polyethylene)), and various evaluations were performed.

[0112] (Examples 3, 7, 16, 25, 26, 34, and 38) Each of the copolymers obtained in Preparation Examples 3, 7, 16, 25, 26, 34, and 38 was dissolved in isoamyl acetate as a solvent to obtain a solution for evaluation (copolymer concentration: 1% by mass). The obtained solution for evaluation was filtered through a filter with a particle removal diameter of 20 nm ("Impact (registered trademark) 8G Disposable Filter" manufactured by Entegris. Material: UPE (ultra-high molecular weight polyethylene)) and various evaluations were performed. The obtained evaluation solution was filtered through a filter with a particle size of 10 nm ("Impact (registered trademark) 8G Disposable Filter" manufactured by Entegris. Material: UPE (ultra-high molecular weight polyethylene)) and various evaluations were performed. Furthermore, the obtained evaluation solution was filtered through a filter with a particle size of 5 nm ("Impact (registered trademark) 8G Disposable Filter" manufactured by Entegris. Material: UPE (ultra-high molecular weight polyethylene)) and various evaluations were performed.

[0113] (Examples 11 to 15, 19 to 21, 23 to 24, 28 to 33, and 35) Each of the copolymers obtained in Preparation Examples 11 to 15, 19 to 21, 23 to 24, 28 to 33, and 35 was dissolved in isoamyl acetate as a solvent to obtain a solution for evaluation (copolymer concentration: 1% by mass). The obtained solution for evaluation was filtered through a filter with a particle removal diameter of 20 nm ("Impact (registered trademark) 8G Disposable Filter" manufactured by Entegris. Material: UPE (ultra-high molecular weight polyethylene)) and various evaluations were performed. The obtained evaluation solution was filtered through a filter with a particle size of 10 nm ("Impact (registered trademark) 8G Disposable Filter" manufactured by Entegris. Material: UPE (ultra-high molecular weight polyethylene)) and various evaluations were performed. Furthermore, the obtained evaluation solution was filtered through a filter with a particle size of 5 nm ("Impact (registered trademark) 8G Disposable Filter" manufactured by Entegris. Material: UPE (ultra-high molecular weight polyethylene)) and various evaluations were performed. The obtained evaluation solution was then filtered through a filter with a particle size of 3 nm ("Impact (registered trademark) 8G Disposable Filter" manufactured by Entegris. Material: UPE (ultra-high molecular weight polyethylene)) and various evaluations were performed.

[0114] (Comparative Examples 1 to 43) Each of the copolymers obtained in Preparation Examples 1 to 43 was dissolved in isoamyl acetate as a solvent to obtain a solution for evaluation (copolymer concentration: 1% by mass). The obtained solution for evaluation was filtered by passing it through a filter with a particle size of 200 nm ("Optimizer (registered trademark) ST" manufactured by Entegris, material: UPE (ultra-high molecular weight polyethylene)), and various evaluations were performed.

[0115] [Table 1]

[0116] [Table 2]

[0117] [Table 3]

[0118] [Table 4]

[0119] [Table 5]

[0120] [Table 6]

[0121] [Table 7]

[0122] [Table 8]

[0123] It can be seen from Tables 3 to 5 that in Examples 1 to 43, in which a solution containing a copolymer was passed through a filter with a particle removal size of 20 nm or less, positive resist compositions from which foreign matter had been sufficiently removed could be prepared. [Industrial Applicability]

[0124] According to the method for producing a positive resist composition of the present invention, it is possible to produce a positive resist composition in which the amount of foreign matter is sufficiently reduced. Furthermore, according to the method of forming a resist pattern of the present invention, a resist pattern in which the amount of foreign matter is sufficiently reduced can be formed.

Claims

1. The following formula (I): 【Chemistry 1】 [In formula (I), R 1 is a halogen atom, a cyano group, an alkylsulfonyl group, an alkoxy group, a nitro group, an acyl group, an alkyl ester group or a halogenated alkyl group, R 2 is an alkyl group, a halogenated alkyl group, or a structure represented by -L-Ar, where L is a single bond or a divalent linking group, and Ar is an aromatic ring group which may have a substituent; R 3 and R 4 are hydrogen atoms, halogen atoms, alkyl groups or halogenated alkyl groups, and may be the same or different. A monomer unit (A) represented by the formula: The following formula (II): 【Chemistry 2】 [In formula (II), R 5 , R 6 , R 8 and R 9 are a hydrogen atom, a halogen atom, a carboxyl group, a halogenated carboxyl group, an alkyl group, or a halogenated alkyl group, and may be the same or different from each other, R 7 is a hydrogen atom, an alkyl group, or a halogenated alkyl group, p and q are integers of 0 to 5, p+q=5, R 6 When a plurality of R 7 When a plurality of are present, they may be the same or different. and filtering a solution containing a solvent and a copolymer having a monomer unit (B) represented by the formula (I) through a filter having a particle size exclusion diameter of 20 nm or less, The weight average molecular weight of the copolymer is greater than 100,000; a total number of fluorine atoms contained in the monomer unit (A) and the monomer unit (B) is 1 or more;

2. forming a resist film using a positive resist composition obtained by the method for producing a positive resist composition according to claim 1; exposing the resist film to light; developing the exposed resist film; A method for forming a resist pattern comprising the steps of:

Citation Information

Patent Citations

  • Positive resist composition and production method thereof, and resist pattern production method using the positive resist composition

    JP2016012104A

  • Copolymer and positive resist composition

    JP2018154754A

  • Resist pattern forming method

    JP2020052144A

  • Positive resist composition, resist film, pattern formation method, and method for manufacturing electronic device

    WO2021153466A1